Dynamics of Mara-Serengeti ungulates in relation to land use changes - Ogutu, Joseph O.; Piepho, Hans-Peter; Dublin, H.T.; Bhola, N.; Reid, Robin S. (Wiley, 2009)
Animal population dynamics can be driven by changing climatic forcing, shifting habitat conditions, trophic interactions and anthropogenic influences. To understand these influences, we analyzed trends in populations of seven ungulate species counted during 15 years (1989–2003) of monthly monitoring using vehicle ground counts in the Maasai Mara National Reserve, Kenya. Abundance of six species declined markedly and persistently throughout the reserve during this period. The declines were contemporaneous with progressive habitat deterioration due to changing land use in pastoral ranches bordering the reserve, habitat desiccation due to rising temperatures, recurrent severe droughts and an exceptional ENSO flood in 1997–1998. The effect of progressive habitat deterioration was accentuated by illicit harvest, competition with livestock and elevated predation. After factoring out the influence of rainfall, ungulate populations declined more markedly in sections of the reserve experiencing greater livestock incursions and poaching. The declines were significantly correlated with increasing number of settlements and people in the pastoral ranches for five species. Heightened predation following a crash in the buffalo Syncerus caffer population during a severe drought in 1993 had little support as the primary cause of the declines.